2021
DOI: 10.9758/cpn.2021.19.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Are Mannan-binding Lectine Serin Protease-2 and Alpha-1-microglobulin and Bukinin Precursor the Potential Biomarkers of Manic Episode? A Study via Urinary Proetomic Analysis

Abstract: Objective: Investigating the molecular basis of bipolar disorder (BD) is crucial in terms of developing effective treatment strategies as well as objective laboratory-based diagnostic tools for the disease. Methods: We examined the urine samples of BD patients both in manic episode and after remission and compared their urinary protein profiles with the controls. Twelve patients and twelve controls (C group) included to the study. Urinary samples of patients were first collected during manic episode (M group) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Yachen Shi et al [73] identified significantly elevated levels of antithrombin III (AT III) expression in plasma of patients with major depression and were listed as candidate biomarkers. In 2021, Cem Cerit et al [74] found that the intensity of AMBP protein discriminated manic episodes in BD patients from remitted and healthy controls, indicating that AMBP protein may be a candidate biomarker for manic episodes in BD patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yachen Shi et al [73] identified significantly elevated levels of antithrombin III (AT III) expression in plasma of patients with major depression and were listed as candidate biomarkers. In 2021, Cem Cerit et al [74] found that the intensity of AMBP protein discriminated manic episodes in BD patients from remitted and healthy controls, indicating that AMBP protein may be a candidate biomarker for manic episodes in BD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Yachen Shi et al [73] identified significantly elevated levels of antithrombin III (AT III) expression in plasma of patients with major depression and were listed as candidate biomarkers. In 2021, Cem Cerit et al [74] found that the intensity of AMBP protein discriminated manic episodes in BD patients from remitted and healthy controls, indicating that AMBP protein may be a candidate biomarker for manic episodes in BD patients. Venn diagram analysis of differential proteins screened under relaxed conditions in a single sample of the depression group compared with the healthy group revealed that 24 differential proteins were co-screened by 13 samples of depression patients, of which 16 differential proteins showed a completely consistent trend of expression in 13 depression patients (Table 6), and 6 differential proteins were related to immunoglobulins (immunoglobulin); 41 differential proteins were co-screened by 12 of 13 depression patient samples(Table S8), and 19 differential proteins showed a completely consistent trend of expression in 12 depression patients, and these results reflected extremely strong consistency.It is worth mentioning that osteopontin (OPN), one of the key molecules involved in neuroinflammation [75] , was screened in both bipolar and depressed groups, and Tingting Li et al [76] showed that blocking osteopontin expression reduced neuroinflammation and alleviated osteopontin depression-like behavior induced by lipopolysaccharide in mice.Kadriu, B. et al [77] found that OPN levels in plasma were significantly lower in patients with major depression.Lee H et al [78] screened biomarkers in plasma that were significantly associated with the severity of depressive symptoms (e.g., anhedonia/retardation): Mannan-binding lectin serine protease 2 (MASP2), and were similarly enriched in the complement activation pathway, which matched the results presented here.Members of the tumor necrosis factor (TNF) superfamily play a role in the pathogenesis of neuropsychiatric disorders because of their relationship with inflammation and neurogenesis, and increases in pro-inflammatory factors such as TNF may be typical of low-grade inflammation in major depressive disorder [79] .…”
Section: Identification Of Urine Proteomementioning
confidence: 99%